Kekuatan Eksekutorial Putusan Majelis Pengadilan Pajak Terhadap Sengketa Pajak di Indonesia (Mimbar Keadilan, 2023)
The purpose of this study is to analyze taxpayers who refuse their legal remedies and do not carry out the decision of the Panel Judge at the Tax Court which is the final decision and has permanent legal force (In kracht Van Gewijsde), and to analyze taxpayers whose legal remedies are granted so that officials the government is obliged to implement the decision of the Panel Judge at the Tax Court. In the laws and regulations general provisions and tax procedures followed by tax laws and regulations, and continued with the formation of formal tax law arrangements and material tax laws, there are 3 (three) tax levies, namely fines, interest, and increases, for related violations with tax obligations, whether late or not yet reporting notification letters (SPT) both periodical and annual, also late or unpaid underpayment of tax payable which should be included if there is an audit result that causes underpayment to become a tax dispute. On the other hand, however, there is an imbalance of interest that should be received by the taxpayer, if there is a refund of the overpayment of tax that is not payable. This study uses a normative juridical method which analyzes using statutory approaches and approaches. The results of this study are to find out that taxpayers are willing to pay off their tax debts and if there are other reasons they can be given the opportunity to repay even though they are subject to additional interest and/or fines, and government officials also carry out fair execution if they have to return overpaid taxes, as well as providing an imbalance of interest if it turns out that there is a delay in returning it because the decision of the Tax Court is final and has permanent legal force.